2001
DOI: 10.1021/bi002661e
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution X-ray Structures of Different Metal-Substituted Forms of Phosphotriesterase from Pseudomonas diminuta,

Abstract: Phosphotriesterase, isolated from the soil-dwelling bacterium Pseudomonas diminuta, catalyzes the detoxification of organophosphate-based insecticides and chemical warfare agents. The enzyme has attracted significant research attention in light of its possible employment as a bioremediation tool. As naturally isolated, the enzyme is dimeric. Each subunit contains a binuclear zinc center that is situated at the C-terminal portion of a "TIM" barrel motif. The two zincs are separated by approximately 3.4 A and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
232
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(241 citation statements)
references
References 19 publications
9
232
0
Order By: Relevance
“…However, the ability of S2ЈC receptors to coordinate Cd 2ϩ in both the native open and closed configurations of the receptor places a restriction on the maximal diameter the pore attains in both states. Using the length of the Cd-S bond (2.1-2.5 Å; (28,29,36,54)), the ionic radius of Cd 2ϩ (0.91 Å), and assuming 5-fold pseudosymmetry in the 5-HT 3A homopentameric receptor, we can estimate a maximum pore diameter of ϳ7 Å if coordination occurs across the receptor pore. If Cd 2ϩ is coordinated by sulfhydryl moieties on adjacent subunits, the pore diameter can be as wide as ϳ11 Å (using the Pythagorean theorem).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ability of S2ЈC receptors to coordinate Cd 2ϩ in both the native open and closed configurations of the receptor places a restriction on the maximal diameter the pore attains in both states. Using the length of the Cd-S bond (2.1-2.5 Å; (28,29,36,54)), the ionic radius of Cd 2ϩ (0.91 Å), and assuming 5-fold pseudosymmetry in the 5-HT 3A homopentameric receptor, we can estimate a maximum pore diameter of ϳ7 Å if coordination occurs across the receptor pore. If Cd 2ϩ is coordinated by sulfhydryl moieties on adjacent subunits, the pore diameter can be as wide as ϳ11 Å (using the Pythagorean theorem).…”
Section: Discussionmentioning
confidence: 99%
“…Although the gating kinetics of the S2ЈC/C316A double mutant appeared to be somewhat slower than S2ЈC, both S2ЈC/C270A (80% Ϯ 5%; n ϭ 6) and S2ЈC/C316A (88% Ϯ 1%; n ϭ 6) mutants were significantly inhibited after exposure to Cd 2ϩ in the open state. We also examined the possible contribution of the negatively charged glutamate at the Ϫ1Ј position (Glu-1Ј) since it has been shown that acidic amino acids can participate in coordinating Cd 2ϩ in metalloproteins (36). Both S2ЈC/E-1ЈN (79 Ϯ 3%; n ϭ 6) and G-2ЈC/E-1ЈN (67 Ϯ 1%; n ϭ 6) appeared to bind Cd 2ϩ equally well as S2ЈC and G-2ЈC, respectively.…”
Section: High Affinity CD 2ϩmentioning
confidence: 99%
“…Second, the putative active site water molecule, which is likely to be present at the product acetate ACT1 O 1 position, lies significantly closer to the zinc ion at the ␣ 1 subsite (1.95 Å) than that at the ␤ site (2.84 Å). This is one striking difference between the active site here and those in other binuclear zinc hydrolases such as the ␣␤ members, where the water/hydroxide ion is almost symmetrically located between the two metal ions (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Therefore, the inhibitory metal ion at the ␣ site may hold the active site water tightly and thus perturb the stereochemical arrangements required for enzyme catalysis as it does in bovine carboxypeptidase A (38).…”
Section: Resultsmentioning
confidence: 88%
“…Based on the binding site(s) of the catalytically essential metal ion(s), we classify these members into four types: ␣␤-binuclear (␣␤), ␣-mononuclear (␣), ␤-mononuclear (␤), and metal-independent subsets. Phosphotriesterase (homology protein), urease, dihydroorotase, renal dipeptidase, isoaspartyl didpeptidase, and dihydropyrimidinase comprise the ␣␤ subset (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Murine adenosine deaminase and Escherichia coli cytosine deaminase belong to the ␣ subset (16,17).…”
mentioning
confidence: 99%
“…In bacteria these usually have either a single transmembrane domain at the C terminus (35) or an N-terminal non-cleaved twin-arginine signal anchor sequence (37). However, bioinformatic analysis supported by structural studies show that OPH has no C-terminal hydrophobic helical domain (38) and the N-terminal signal peptide of OPH is cleaved off during biosynthesis and therefore cannot serve as a signal anchor (15).…”
Section: Oph Is Tightly Bound To the B Diminuta Inner Membrane-mentioning
confidence: 99%